use identity (1.1m-0.4) (1.1+0.4)
Answers
Answered by
95
Hi ,
we know the algebraic identity ,
( a - b ) ( a + b ) = a² - b²
( 1.1 - 0.4 ) ( 1.1 + 0.4 )
= ( 1.1 )² - ( 0.4 )²
= 1.21 - 0.16
= 1.05
I hope this helps you.
:)
we know the algebraic identity ,
( a - b ) ( a + b ) = a² - b²
( 1.1 - 0.4 ) ( 1.1 + 0.4 )
= ( 1.1 )² - ( 0.4 )²
= 1.21 - 0.16
= 1.05
I hope this helps you.
:)
Answered by
37
here is your answer
hope you like it.
Attachments:
![](https://hi-static.z-dn.net/files/d11/d0c126125409d11bec781fa2c529fc0a.jpg)
Similar questions
Science,
9 months ago
Environmental Sciences,
1 year ago
History,
1 year ago
Science,
1 year ago
Math,
1 year ago